TEACHING GERMAN IMPERATIVE ACCORDING TO THE ACTIVE LEARNING APPROACH - Fatma KARAMAN (Fırat University, 2019)
The innovations taking place in education and training every other day have made it necessary for teachers to question their methods and techniques they're applying, adapt what the new age brings and also be able to meet the students' expectations. Because students are not as passive-takers anymore; instead they became such i